Становлення державної служби Карпатської України крізь призму українсько-чехословацьких відносин (1938–1939 рр.) - Вегеш, М.; Віднянський, С.; Чаварга, А. (Український історичний журнал, 2022)
Мета статті полягає у вивченні національного складу державних службовців Карпатської України на етапі становлення державності в 1938–1939 рр. Методологічну основу дослідження становлять принципи історизму, які дозволяють об’єктивно підійти до вивчення суспільних процесів, подій і фактів. Використано аналітичний, порівняльний, системний і конкретно- історичний методи. Наукова новизна. Розглянуто акт складання присяги на вірність державі службовцями Підкарпатської Русі – Карпатської України як особливу форму державного правління; проаналізовано випадки зловживання владою або службовим становищем урядниками чеської національності щодо українського населення Карпатської України; з’ясовано, якими були причини переміщення державних службовців чеської та словацької національностей із Карпатської України до Чехії, Словаччини, Моравії; розглянуто правове реґулювання цього питання; встановлено, яким був національний склад урядників Карпатської України (на прикладі Міністерства економічних справ, де працювали до 600 службовців). Висновки. Вперше в українській історіографії наводиться й аналізується текст присяги на вірність Чехословацькій Республіці, яку складали державні службовці Підкарпатської Русі, а також присяги вищих урядовців та послів на вірність незалежній Карпатській Україні. Доведено, що клятва на вірність Чехословаччині не передбачала вірності народам цієї держави, адже дуже часто службовці зловживали своїм становищем і діяли всупереч інтересам населення, яке мали представляти. Досліджено причини та мотивацію переміщення держслужбовців чеської і словацької національностей із Карпатської України до Чехії, Словаччини, Моравії. Встановлено, яким був національний склад Міністерства економічних справ Карпатської України. The issue of formation of the civil service in Carpathian Ukraine is considered in the article. The purpose of the article is to study the national composition of civil servants of Carpathian Ukraine at the stage of formation of Ukrainian statehood. The methodological basis of the study is the principles of historicism, which allow an objective approach to the study of social processes, events and facts. The authors used analytical, comparative, systematic and concretehistorical methods. Scientific originality. The act of taking the oath of allegiance to the state by the officials of Subcarpathian Rus and Carpathian Ukraine as a special form of government was considered; cases of abuse of power or official position by Czech officials against the Ukrainian population of Carpathian Ukraine were analysed (based on official documents of Carpathian Ukraine); the reasons for the transfer of Czech and Slovak civil servants from Carpathian Ukraine to the Czechia, Slovakia and Moravia were clarified; the legal regulation of this issue is considered; it was established what was the national composition of officials of Carpathian Ukraine (on the example of the Ministry of Economic Affairs of Carpathian Ukraine). Conclusions. The text of the oath of allegiance to the Czechoslovak Republic, which was taken by civil servants of Subcarpathian Rus, as well as the oath of allegiance of senior government officials and ambassadors to independent Carpathian Ukraine is analyzed for the first time in Ukrainian historiography. It is proved that the oath of allegiance to the Czechoslovak Republic did not presuppose allegiance to the peoples of this state, because the officials very often abused their official position and acted against the interests of the population, which they were supposed to represent. This is evidenced by cases of abuse, harassment and even intimidation of the local Ukrainian population by the Czech officials. The reasons and motivation for the transfer of civil servants of Czech and Slovak nationalities from Carpathian Ukraine to the Czechia, Slovakia or Moravia have been studied. It was possible to establish the national composition of the Ministry of Economic Affairs of Carpathian Ukraine.